Understanding the Unique Needs of Adolescent Refugee Students - Bobette Bouton (Middle Grades Review, 2016)
Using the Essential Attributes of developmentally responsive, challenging, empowering, and equitable guidelines established by This We Believe: Keys to Educating Young Adolescents, this article will provide a frame of reference for readers to assist their understanding of the kaleidoscope of issues that face our refugee adolescent population (AMLE/NMSA, 2010). For each of the four essential attributes, practical application for the middle grades classroom is offered. These ideas are to assist teachers in meeting the needs of their students who come from a refugee background and to give a foundation in an area that is often overlooked in the current educational system.
Keywords: refugee; adolescent; trauma; empathy